Bentuk dan Komponen Penentu Kompensasi Eksekutif - Diaz, Marsela; Espa, Vitriyan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2008)
This Article discusses executive compensation from agency conflict conception, plan of executive compensation definition, target the of this compensation plan, variety of compensation. Every company has different policy in case of compensation gift/giving to its all manager and executive, either in case of its compensation form or determinant. The most form of executive compensation that recognized at this time is Stock Option Program (SOP), given as bonus to executives to minimization conflict of interest between shareholder and management. This SOP usually given base managerial performance like accountancy profit, shore price and also earning shares (EPS), finance performance like return on equity (ROE) and return on asset (ROA), company size and corporate growth. Keywords: Compensation Executive, Stock Option Program, Performance Managerial